Geriatric nutrition risk index in the prediction of all-cause and cardiovascular mortality in elderly hypertensive population: NHANES 1999–2016 - Huo, Xuan; Wu, Meiyin; Gao, Dongmei; Zhou, YueShengzi; Han, Xu; Lai, Weilin; Wang, Mengqi; Hang, Yilun (Frontiers in Cardiovascular Medicine, 2023)
Background Hypertension is a major risk factor for the global burden of disease, and nutrition is associated with an increased risk of mortality from multiple diseases. Few studies have explored the association of nutritional risk with all-cause mortality and cardiovascular mortality in hypertension, and our study aims to fill this knowledge gap. Method We included data from the National Health and Nutrition Examination Survey (NHANES) from 1999 to 2016 on a total of 10,037 elderly patients with hypertension. The nutritional status was evaluated using the Geriatric Nutrition Risk Index (GNRI). Kaplan-Meier survival analysis was performed to analyze the survival rates of different nutritional risk groups. COX proportional risk regression models were used to analyze the predictive effect of GNRI on all-cause mortality and cardiovascular mortality in hypertensive patients. Restricted cubic splines (RCS) were used to explore the nonlinear relationship between GNRI and mortality. Result The mean age of the hypertensive patients was 70.7 years. A total of 4255 (42.3%) all-cause mortality and 1207 (17.2%) cardiovascular mortality occurred during a median follow-up period of 106 months. Kaplan-Meier showed a more significant reduction in survival for the moderate to severe malnutrition risk of GNRI. The adjusted COX proportional hazards model showed that the hazard ratios for all-cause mortality and cardiovascular mortality in the moderate to severe malnutrition risk group for GNRI were 2.112 (95% CI, 1.377,3.240) and 2.604 (95% CI, 1.603,4.229), respectively. The RCS showed that increased GNRI was associated with a reduced risk of all-cause mortality and cardiovascular mortality risk reduction. Conclusion Malnutrition exposure assessed by GNRI effectively predicts the risk of all-cause mortality and cardiovascular mortality in the elderly with hypertension.